2017
DOI: 10.18632/oncotarget.15540
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated fibroblasts decrease tumor cell susceptibility to NK cell-mediated killing through matrix-metalloproteinases secretion

Abstract: Cancer-associated fibroblasts (CAFs) play a central role in the complex process of tumor-stroma interaction and promote tumor growth. Emerging evidences also suggest that these fibroblasts are involved in the alteration of the anti-tumor immune response by impacting several immune cell populations, especially through their secretion of pro-inflammatory and immunosuppressive factors in the tumor microenvironment. However, the underlying immuno-modulating mechanisms triggered by these fibroblasts are still only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 61 publications
2
77
0
Order By: Relevance
“…S100 calcium binding protein A4 (S100A4), also known as fibroblast-specific protein 1 (FSP1), for example, is a marker that has been used in a number of publications in order to confirm the CAF phenotype of examined cells. [49][50][51] However, recent studies have raised some suspicion on the specificity of FSP1, as it has been observed to be less reliable for fibroblast identification from primary tumor samples than FAP. 25 It has also been confirmed to be expressed by metastatic prostate cancer-derived epithelial cell lines and tissues.…”
Section: Other Markersmentioning
confidence: 99%
“…S100 calcium binding protein A4 (S100A4), also known as fibroblast-specific protein 1 (FSP1), for example, is a marker that has been used in a number of publications in order to confirm the CAF phenotype of examined cells. [49][50][51] However, recent studies have raised some suspicion on the specificity of FSP1, as it has been observed to be less reliable for fibroblast identification from primary tumor samples than FAP. 25 It has also been confirmed to be expressed by metastatic prostate cancer-derived epithelial cell lines and tissues.…”
Section: Other Markersmentioning
confidence: 99%
“…MICA/B work as the two ligands of NKG2D, express at the surface of tumour cells. Ziani et al showed that the increasing secretion of matrix metalloproteinases (MMPs) by CAFs in the melanoma tumour microenvironment could reduce the expression of MICA/B, therefore further decreasing the cytotoxic activity of NK cells to melanoma cancer cells which depended on NKG2D . Compared to the normal endometrial fibroblasts (NEFs), the expression of poliovirus receptor (PVR) was downregulated in CAFs .…”
Section: Crosstalk Between Cancer‐associated Fibroblasts and Immune Cmentioning
confidence: 99%
“…Indeed, the cellular composition of regression includes tumour-associated macrophages and cancerassociated fibroblasts that are known to play a crucial role in tumour promotion. Conversely, tumourinfiltrating lymphocytes undoubtedly have antitumoural effects within the melanoma-derived microenvironment (Ziani et al 2017). Along these lines, regression may be considered a paradoxical one step forward to loco-regional and distant metastases.…”
Section: Main Clinical Types Of Primary Melanomamentioning
confidence: 99%